Analysis of the energy propagation in the keyhole plasma arc welding using a novel fully coupled plasma arc-keyhole-weld pool model. (October 2019) - Wu, Dongsheng; Tashiro, Shinichi; Hua, Xueming; Tanaka, Manabu
Highlights: A novel fully coupled plasma arc-keyhole-weld pool model is developed for the KPAW process in the quasi-steady state. The coupled interaction between the forces and energy propagation is revealed. The energy efficiency in the KPAW process is calculated and analyzed. Abstract: The distribution of the energy in the keyhole plasma arc welding process has significant effect on the final weld quality. In this study, a novel fully coupled plasma arc-keyhole-weld pool model is built to study the energy propagation in the keyhole plasma arc welding process. The numerical results show that: the conduction energy flux, electric energy flux and total energy flux from the arc to the top weld pool are larger than these from the arc to the bottom weld pool. Under the influence of the arc pressure and plasma shear stress, two dominant convective eddies exist inside the weld pool, and the molten metal flows backward at the top and bottom surfaces, so the energy is not accumulated on the top surface, but transported to the rear weld pool together with the molten metal. The conduction energy from the arc to the anode is much higher than the thermionic heating. The penetrated keyhole formation can't increase the energy absorption, and 11.5% of the arc energy are lost by the efflux arc. The calculated energy efficiency for heating the anode in this study is only 60.7%.